2002
DOI: 10.1081/ddc-120003853
|View full text |Cite
|
Sign up to set email alerts
|

Alginate in Drug Delivery Systems

Abstract: Alginates are established among the most versatile biopolymers, used in a wide range of applications. The conventional use of alginate as an excipient in drug products generally depends on the thickening, gel-forming, and stabilizing properties. A need for prolonged and better control of drug administration has increased the demand for tailor-made polymers. Hydrocolloids like alginate can play a significant role in the design of a controlled-release product. At low pH hydration of alginic acid leads to the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
639
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,287 publications
(650 citation statements)
references
References 83 publications
5
639
0
6
Order By: Relevance
“…The formulations are used for various purposes: immobilization of cellular organisms and enzymes, application of biological control agents and mycoherbicides, increase the stability of recombinant plasmids in host cells, bacterial chemotaxis research, mushroom cultivation (Prasad and Kadokawa 2009), and a primary polymer in formulations of drugs (Tonnesen and Karlsen 2002). Alginate is a naturally occurring polymer available mainly from different marine macroalgae in large sustainable quantities (Draget et al 2002;Yabur et al 2007), as well as from several bacteria (Sabra et al 2001;Trujillo-Roldán et al 2003).…”
Section: Macro-and Micro-formulations Of Alginatementioning
confidence: 99%
“…The formulations are used for various purposes: immobilization of cellular organisms and enzymes, application of biological control agents and mycoherbicides, increase the stability of recombinant plasmids in host cells, bacterial chemotaxis research, mushroom cultivation (Prasad and Kadokawa 2009), and a primary polymer in formulations of drugs (Tonnesen and Karlsen 2002). Alginate is a naturally occurring polymer available mainly from different marine macroalgae in large sustainable quantities (Draget et al 2002;Yabur et al 2007), as well as from several bacteria (Sabra et al 2001;Trujillo-Roldán et al 2003).…”
Section: Macro-and Micro-formulations Of Alginatementioning
confidence: 99%
“…The potential use of the diferent alginate hydrogels as pharmaceutical excipients has not yet been fully evaluated but alginate is likely to make an important contribution in the development of polymeric delivery systems. The precise chemical degradation mechanism and approaches in the choice of alginate for drug deliveries was previously broadly reviewed [113]. Leor et al have suggested that intra-myocardial injection of alginate induces neo-vascularization and improved LV function [28,110].…”
Section: Lim Et Al Related That Their Results On Poly(l-lactic Acid)mentioning
confidence: 99%
“…A linear polymer consisting of D-mannuronic acid and L-guluronic acid residues arranged in blocks in the polymer chain, these homogeneous blocks (composed of either acid residue alone) are separated by blocks made of random or alternating units of mannuronic and guluronic acids. Alginates offer various applications in drug delivery, such as in matrix type alginate gel beads, in liposomes, in modulating gastrointestinal transit time, for local applications and to deliver the bio molecules in tissue engineering applications [45] (fig. 3).…”
Section: Alginatesmentioning
confidence: 99%